2006
DOI: 10.1128/jb.01740-05
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Overexpression of Wild-Type and Mutant hipA Genes in Escherichia coli : Effects on Macromolecular Synthesis and Persister Formation

Abstract: Persistence is an epigenetic trait that allows a small fraction of bacteria, approximately one in a million, to survive prolonged exposure to antibiotics. In Escherichia coli an increased frequency of persisters, called "high persistence," is conferred by mutations in the hipA gene, which encodes the toxin entity of the toxin-antitoxin module hipBA. The high-persistence allele hipA7 was originally identified because of its ability to confer high persistence, but little is known about the physiological role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
204
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(215 citation statements)
references
References 37 publications
9
204
2
Order By: Relevance
“…In contrast, in a hipB þ strain, cells are fully rescued from the toxic effect of HipA expression (Fig. 1B), in agreement with previous observations (23). But whereas the number of colonies was not affected by HipA in the presence of HipB, their growth dynamics were, and some of the colonies appeared over an extended period of time, compared to colonies that did not express HipA, as apparent also in ref.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…In contrast, in a hipB þ strain, cells are fully rescued from the toxic effect of HipA expression (Fig. 1B), in agreement with previous observations (23). But whereas the number of colonies was not affected by HipA in the presence of HipB, their growth dynamics were, and some of the colonies appeared over an extended period of time, compared to colonies that did not express HipA, as apparent also in ref.…”
Section: Resultssupporting
confidence: 81%
“…We induced HipA expression in cells for 3 h and plated them in conditions in which the HipA expression was repressed. We found that, without HipB, even leakage levels of expression of HipA interrupts cell growth and prevents the subsequent appearance of colonies, as previously observed (23,24). In contrast, in a hipB þ strain, cells are fully rescued from the toxic effect of HipA expression (Fig.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The persister cells do not contain genetic traits that confer resistance to antibiotics, and, as a result, the progeny of these persisters are just as sensitive to the antibiotic used to treat the parental cells (Korch & Hill, 2006;Stewart, 2002). Although oxacillin tolerance was reduced in the dnaK mutant of meticillin-resistant S. aureus strain COL, no such reduction in the oxacillin MIC was observed in the dnaK mutant of meticillin-susceptible S. aureus strain SH1000.…”
Section: Involvement Of Dnak In Induction Of Thermotolerancementioning
confidence: 72%